Rút gọn biểu thức: N = (3a + 2) ² + 2(2 + 3a)(1 – 2b) + (2b – 1) ²

Question

Rút gọn biểu thức:
N = (3a + 2) ² + 2(2 + 3a)(1 – 2b) + (2b – 1) ²

in progress 0
Gianna 4 tháng 2021-08-23T07:58:44+00:00 2 Answers 106 views 0

Answers ( )

    0
    2021-08-23T07:59:51+00:00

    Đáp án:

     

    Giải thích các bước giải:

     .

    0
    2021-08-23T07:59:51+00:00

    Đáp án:

     

    Giải thích các bước giải:

     N=(3a+2)²+2(2+3a)(1-2b)+(2b-1)²

      =(3a+2)²-2(2+3a)(2b-1)+(2b-1)²

     = (3a+2-2b+1)²

    =(3a-2b+3)²

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )